2023
DOI: 10.1002/celc.202201145
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polymer/Graphene‐based Composites for Next Generation Energy Storage and Sensing Applications

Abstract: Growing environmental and health demands along with the deficiency of conventional energy sources result in the need for alternative solutions in the field of energy storage and analyte detecting systems. To address these issues, a significant increase in research interest for novel composite materials has been observed in recent years. Conductive polymers and graphene‐based composites have emerged as promising electrode materials for supercapacitors and electrochemical sensors due to their improved electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 154 publications
(259 reference statements)
0
4
0
Order By: Relevance
“…They have great importance in our daily lives because of their distinctive characteristics, such as high porosity and lightweight, which have led to the possibility of using them in thermal insulation, packaging, and even sound insulation. However, their use is still minimal due to the large size of the pores and the low number of functional groups they have [93]. In recent studies, it was found that the addition of the polymer to the graphene aerogel significantly improves its properties [94].…”
Section: Graphene-based Materials/polymer Composite Aerogelsmentioning
confidence: 99%
“…They have great importance in our daily lives because of their distinctive characteristics, such as high porosity and lightweight, which have led to the possibility of using them in thermal insulation, packaging, and even sound insulation. However, their use is still minimal due to the large size of the pores and the low number of functional groups they have [93]. In recent studies, it was found that the addition of the polymer to the graphene aerogel significantly improves its properties [94].…”
Section: Graphene-based Materials/polymer Composite Aerogelsmentioning
confidence: 99%
“…Polymer/graphene composite: There are various methodologies to form graphene filled different polymer composites. Polymers inapposite for in situ polymerization approach, could be employed shaping graphene-based polymer nanocomposite broadly using melt intercalation polymerization methodology have been already reported [101][102][103].…”
Section: Chemical Modificationmentioning
confidence: 99%
“…[37][38][39][40][41][42]; dedicated sensors for environmental monitoring by the detection of pollutants in water, including heavy ions [43,44]; finalizing with food and drug analyses [45,46]. The second main application of the hybrid structures obtained from graphene and conducting polymers, occurring mainly in the last 10 years, is related to photovoltaic energy generation and energy storage applications/supercapacitors [47][48][49] as well as other photocatalytic applications [50].…”
Section: Introductionmentioning
confidence: 99%